(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe physical activity levels, anthropometric characteristics, and selected biochemical markers of office workers prior to the implementation of a workplace physical activity intervention. Methods: A cross-sectional descriptive study was conducted among 66 office employees. Physical activity was assessed using the IPAQ-SF and calculated directly from raw data according to the standard scoring protocol, expressed as MET-minutes/week. Results: The mean age was 36.2 ± 9.1 years, with equal distribution of males and females. The mean BMI was 23.3 ± 3.4 kg/m², and 27.3% were classified as overweight or obese. The median total physical activity was 1,148 (688-2,314) MET-minutes/week. The proportions of low, moderate, and high physical activity levels were 16.7%, 72.7%, and 10.6%, respectively. No significant difference in total MET was observed by sex (p = 0.462) or age group (p = 0.331). Participants with normal BMI had significantly higher physical activity levels than those with overweight/obesity (p = 0.041). Mean LDL-C was 3.38 ± 0.94 mmol/L; HDL-C 1.29 ± 0.24 mmol/L; and serum uric acid 357.6 ± 86.4 µmol/L. Conclusion: Most office employees achieved a moderate level of physical activity; however, the prevalence of overweight/obesity and metabolic indicators approaching risk thresholds remains a concern.